Psychological factors and treatment effectiveness in resistant anxiety disorders in highly comorbid inpatients - Ociskova M; Prasko J; Latalova K; Kamaradova D; Grambal A (Neuropsychiatric Disease and Treatment, 2016)
Marie Ociskova, Jan Prasko, Klara Latalova, Dana Kamaradova, Ales Grambal Department of Psychiatry, Olomouc University Hospital, Faculty of Medicine and Dentistry, Palacký University Olomouc, Czech Republic Background: Anxiety disorders are a group of various mental syndromes that have been related with generally poor treatment response. Several psychological factors may improve or hinder treatment effectiveness. Hope has a direct impact on the effectiveness of psychotherapy. Also, dissociation is a significant factor influencing treatment efficiency in this group of disorders. Development of self-stigma could decrease treatment effectiveness, as well as several temperamental and character traits. The aim of this study was to explore a relationship between selected psychological factors and treatment efficacy in anxiety disorders. Subjects and methods: A total of 109 inpatients suffering from anxiety disorders with high frequency of comorbidity with depression and/or personality disorder were evaluated at the start of the treatment by the following scales: the Mini-International Neuropsychiatric Interview, the Internalized Stigma of Mental Illness scale, the Adult Dispositional Hope Scale, and the Temperament and Character Inventory – revised. The participants, who sought treatment for anxiety disorders, completed the following scales at the beginning and end of an inpatient-therapy program: Clinical Global Impression (objective and subjective) the Beck Depression Inventory – second edition, the Beck Anxiety Inventory, and the Dissociative Experiences Scale. The treatment consisted of 25 group sessions and five individual sessions of cognitive behavioral therapy or psychodynamic therapy in combination with pharmacotherapy. There was no randomization to the type of group-therapy program. Results: Greater improvement in psychopathology, assessed by relative change in objective Clinical Global Impression score, was connected with low initial dissociation level, harm avoidance, and self-stigma, and higher amounts of hope and self-directedness. Also, individuals without a comorbid personality disorder improved considerably more than comorbid patients. According to backward-stepwise multiple regression, the best significant predictor of treatment effectiveness was the initial level of self-stigma. Conclusion: The initial higher levels of self-stigma predict a lower effectiveness of treatment in resistant-anxiety-disorder patients with high comorbidity with depression and/or personality disorder. The results suggest that an increased focus on self-stigma during therapy could lead to better treatment outcomes. Keywords: anxiety disorders, self-stigma, hope, personality, dissociation, treatment effectiveness